Experimental study on combustion and emission characteristics of iso-butanol/diesel and gasoline/diesel RCCI in a heavy-duty engine under low loads. (1st February 2020) - Pan, Suozhu; Liu, Xingwen; Cai, Kai; Li, Xin; Han, Weiqiang; Li, Bolun
Highlights: The combustion and emission characteristics of iso-butanol/diesel RCCI were studied. The iso-butanol/diesel RCCI has a better power recovery ability than gasoline/diesel RCCI. The iso-butanol/diesel RCCI has higher ITE compared with gasoline/diesel RCCI at test conditions. The gasoline/diesel and iso-butanol/diesel RCCI can break the trade-off relationship between NOx and PM emissions. The iso-butanol/diesel RCCI achieves lower CO, HC, NOx and PM emissions Compared with the gasoline/diesel RCCI. Abstract: This work experimentally studies the combustion and emission of iso-butanol/diesel RCCI (Reactivity Controlled Compression Ignition) under low loads and compares its results with gasoline/diesel RCCI. The results show that iso-butanol/diesel RCCI has better power recovery ability than gasoline/diesel RCCI. When Rp (Premixed Ratio) is 50% and 60%, IMEP (Indicated Mean Effective Pressure) of iso-butanol/diesel RCCI is 1.4% and 3.9% higher than maximum IMEP of CCM (Conventional Combustion Mode) respectively. Both iso-butanol/diesel and gasoline/diesel RCCI contain LTHR (Low Temperature Heat Release) and HTHR (High Temperature Heat Release). With increase of Rp in both RCCI combustion modes, combustion phase retard, peak value of heat release and maximum PRR (Pressure Rising Rate) decrease, ID (ignition delay), CD (combustion duration), CA50-CA10, maximum mean in-cylinder temperature and ITE (Indicated Thermal Efficiency) increase. Compared with the gasoline/diesel RCCI, iso-butanol/diesel RCCI has later combustion phase, longer ID, CD and CA50-CA10, higher maximum mean in-cylinder temperature and ITE, as well as lower maximum PRR. Furthermore, with increase of Rp, CO (Carbon Monoxide), NOx (Nitrogen Oxides) and PM (Particulate Matter) emissions decrease, HC (Hydrocarbon) increases for both gasoline/diesel and iso-butanol/diesel RCCI. Compared with the gasoline/diesel RCCI, iso-butanol/diesel RCCI achieves lower CO, HC, NOx and PM emissions.